Introducing wearable haptics for rendering velocity feedback in VR serious games for neuro-rehabilitation of children - Camardella, Cristian; Chiaradia, Domenico; Bortone, Ilaria; Frisoli, Antonio; Leonardis, Daniele (Frontiers in Virtual Reality, 2023)
Rehabilitation in Virtual Reality offers advantages in terms of flexibility and parametrization of the exercises, repeatability, and continuous data recording and analysis of the progress of the patient, also promoting a high engagement and cognitive challenges. Still, the most of the proposed virtual settings provide a high quality, immersive visual and audio feedback, without involving the sense of touch. In this paper, we show the design, implementation and first evaluation of a gaming scenario for upper limb rehabilitation of children with cerebral palsy. In particular we took care to introduce the haptic feedback as a useful source of sensory information for the proposed task, considering at the same time the strict constraints for the haptic wearable devices to comply with patient's comfort, residual motor abilities, and with the embedded tracking features of the latest VR technologies. To show the potential of haptics in a rehabilitation setup, the proposed device and rendering method has been used to improve velocity control of upper limb movements during the VR exercise, given its importance as a motor recovery metric. Eight healthy participants have been enrolled and results showed that the haptic feedback can lead to lower speed tracking errors and a higher movement smoothness, making the proposed setup suitable to be used in a rehabilitation context as a way to promote movement fluidity during exercises.